Manejo da fertilidade do solo sobre o crescimento radicular do capim marandu e interação com fungos micorrízicos - Sousa, Andressa da Luz (Universidade Federal do Tocantins, 2023)
The objective of this work was to evaluate the effect of soil fertility management, with fertilization, liming and plastering, on the chemical attributes of the soil, as well as on the root growth of marandu grass and the interaction of forage with arbuscular mycorrhizal fungi (AMFs) natives. The experiment was conducted at the Agropastoril Frutins farm, located in the municipality of Araguaína - TO, starting in October 2021 and the samplings carried out in April 2022. The experiment was conducted in plots of 30 m2 (5 x 6 m), in a randomized block design - CBD, with four replications. There were seven treatments: There were seven treatments: Control (without soil correction or fertilization), fertilization with NPK, fertilization with NPK plus liming and four more treatments with the combination of fertilization plus lime with four doses of gypsum (200, 750, 1500 and 2250 kg ha- 1). Liming and plastering altered the chemical characteristics of the soil at the studied depths (0 – 20 e 20 – 40), reduced aluminum saturation and increased Ca content and pH in the soil profile. Gypsum increased root dry matter production only at the 200 kg ha-1 dose. Soil fertility management negatively influenced the colonization and sporulation of arbuscular mycorrhizal fungi.